Converging trajectories? Reassessing EU Cohesion Policy in times of new industrial policy - Francesco Molica (European Commission, Joint Research Centre (JRC), 2023)
The paper presents a critical assessment of EU Cohesion Policy's rationale and specific features through the lenses of theories loosely referred to as "new industrial policy". Theoretical work in this areas is important in order to clarify the role of Cohesion Policy in the context of the current revival of industrial policies and their growing importance for Europe's economic, geopolitical, technological and climate ambitions. The paper explores the main challenges Cohesion Policy should address in order to fully embrace the experimentalism and directionality entailed in new industrial policy, going beyond the limitations of Smart Specialisation Strategies in reflecting this perspective. At the same time, a set of arguments is presented in support to the idea that the new industrial policy paradigm can help Cohesion Policy refocus its limping rationale and regain political prominence.
Keywords: 330; Cohesion Policy; European Union; Smart Specialisation Strategy; Industrial Policy